Diagnosis and management of osteomyelitis - Gunawan, Gunawan; Setiyohadi, Bambang (Indonesian Rheumatology Association, 2010)
Osteomyelitis is an infection of the bone that causes bone destruction and formation of new bone as the result of the infl ammatory process. Proper diagnosis in osteomyelitis is important since it determines the decision-making in the management of the disease: whether to perform aggressive treatments or administration of long-term antibiotic treatment. Imaging techniques play an important role in the diagnosis of osteomyelitis, but their results should be interpreted with care as they have a wide range of sensitivity and specifi city. A combination of imagingtechniques could improve their sensitivity and specifi city. Conventional radiography is an affordable and widely available technique, and has been proven to be usefulÂ in diagnosing and excluding the differential diagnosesof osteomyelitis. Surgical intervention to remove necrotic tissues and administration of antibiotics to eradicate pathogens are necessary in the anagementof osteomyelitis. Several antibiotics such as quinolones,rifampin, and clindamycin have been proven to havegood penetration into bone.